Gradual PVP leaching from PVDF/PVP blend membranes and its effects on membrane fouling in membrane bioreactors - Marbelia, L. (2019)
Improving the hydrodynamics on the membrane surface in a magnetically induced membrane vibration system (MMV) has been proven efficient for membrane fouling control in membrane bioreactors. This advantage can be further extended by using an optimized membrane. This was realized in this study by preparing porous polyvinylidene fluoride membranes via polyvinylpyrrolidone (PVP) blending and later by leaching out the PVP from the membrane matrix via post-treatment using NaOCl. Results show that increasing the PVP content in the casting solution increases membrane fouling resistance. Slowly leaching of PVP after several periodic NaOCl cleanings increased membrane permeance. No advantage of NaOCl post-treatment was observed. The long-term filtration confirmed the superiority of the highly porous membrane that complemented the advantages offered by the MMV system. This suggests that despite the small quantity of the remaining PVP, its leaching offered a substantial gain to improve membrane filterability. Â© 2018 Elsevier B.V.